Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.rse.2011.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring gradual ecosystem change using Landsat time series analyses: Case studies in selected forest and rangeland ecosystems

Abstract: Monitoring gradual ecosystem change using Landsat time series analyses: Case studies in selected forest and rangeland ecosystems" (2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 69 publications
2
120
0
3
Order By: Relevance
“…The damage to vegetation caused by fire results in a significant decrease of the NDVI. Because of its applicability to a wide range of sensors, including those lacking SWIR bands, its simplicity and relatively good performance, NDVI has been used extensively to map burned areas, assess burn severity and monitor vegetation recovery [7,14,[55][56][57]. Similar to NDVI, GEMI uses the visible red and near infrared domains but was designed following a non-linear approach in an attempt to reduce undesired atmospheric effects.…”
Section: Index Full Name Abbreviation Equation Referencementioning
confidence: 99%
“…The damage to vegetation caused by fire results in a significant decrease of the NDVI. Because of its applicability to a wide range of sensors, including those lacking SWIR bands, its simplicity and relatively good performance, NDVI has been used extensively to map burned areas, assess burn severity and monitor vegetation recovery [7,14,[55][56][57]. Similar to NDVI, GEMI uses the visible red and near infrared domains but was designed following a non-linear approach in an attempt to reduce undesired atmospheric effects.…”
Section: Index Full Name Abbreviation Equation Referencementioning
confidence: 99%
“…, in the study that developed the harmonic modeling approach we adapted to detect microrefugia, demonstrated that dense time series of all available Landsat data enabled detection of subtle forest thinning. Other studies, more commonly using time series of annual images (including composite images; eg, Roy et al, 2010), emphasize the power of LTS to detect gradual processes including forest decline due to diffuse disturbances such as insect outbreaks or drought (Ahmed et al, 2017;Cohen et al, 2016;Deel et al, 2012;Kennedy et al, 2010), forest succession and woodland densification (Vogelmann et al, 2012), and variation in ecosystem recovery following disturbance (Kennedy et al, 2007(Kennedy et al, , 2010Lawrence and Ripple, 1999;Storey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights the benefits of using Landsat satellite imagery to detect, quantify and understand the trend in land cover change in forest environments. Vogelmann et al (2012) discuss the use of Landsat imagery for forest change analysis and they depict that Landsat imagery is applicable for detecting abrupt and gradual ecosystem changes. However in order to get more accurate result among forest disturbance is recommended to use annual time series images.…”
Section: Discussionmentioning
confidence: 99%